2011
DOI: 10.2486/indhealth.ms1291
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Infrared Tympanic Temperature for the Evaluation of Heat Strain While Wearing Impermeable Protective Clothing in Hot Environments

Abstract: The purpose of this study was to investigate the validity of infrared tympanic temperature (IR T ty ) as a thermal index to evaluate the heat strain of workers in hot environments, in comparison with rectal temperatures at various depths (T re-4, -8, and -16 for 4, 8 and 16 cm from the anal sphincter). Eight males underwent twelve experimental conditions: two activities (rest and exercise) × three clothing levels [Control, HDPE (high-density polyethylene coverall) and PVC (polyvinyl chloride coverall) conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Sublingual: Linder and Carmichael (1935), Ivy (1944), Barcroft and Edholm (1946), Consolazio et al (1963), , Fox et al (1973b), Collins et al (1977), Edwards et al (1978), Erickson (1980), Kolanowski and Gunter (1981), Ilsley et al (1983), Mairiaux et al (1983), Thatcher (1983), Baker et al (1984), Eriksson et al (1985), Keilson et al (1985), Terndrup et al (1989), Darowski et al (1991), Marion et al (1991), Mackowiak et al (1992), Maw and Taylor (1992), Castle et al (1993), McGann et al (1993, Nakamura et al (1997). Auditory canal: Edwards et al (1978), Terndrup et al (1989), Darowski et al (1991), Chamberlain et al (1995), Shibasaki et al (1998), Childs et al (1999), Easton et al (2007), Jay et al (2007b), Nagano et al (2010), Lee et al (2011), Taylor (2012. Liver: Graf (1959).…”
Section: Comparisons Among Measurement Sitesmentioning
confidence: 95%
See 1 more Smart Citation
“…Sublingual: Linder and Carmichael (1935), Ivy (1944), Barcroft and Edholm (1946), Consolazio et al (1963), , Fox et al (1973b), Collins et al (1977), Edwards et al (1978), Erickson (1980), Kolanowski and Gunter (1981), Ilsley et al (1983), Mairiaux et al (1983), Thatcher (1983), Baker et al (1984), Eriksson et al (1985), Keilson et al (1985), Terndrup et al (1989), Darowski et al (1991), Marion et al (1991), Mackowiak et al (1992), Maw and Taylor (1992), Castle et al (1993), McGann et al (1993, Nakamura et al (1997). Auditory canal: Edwards et al (1978), Terndrup et al (1989), Darowski et al (1991), Chamberlain et al (1995), Shibasaki et al (1998), Childs et al (1999), Easton et al (2007), Jay et al (2007b), Nagano et al (2010), Lee et al (2011), Taylor (2012. Liver: Graf (1959).…”
Section: Comparisons Among Measurement Sitesmentioning
confidence: 95%
“…Indeed, due to the curvature of the auditory canal and the presence of cerumen (ear wax), infrared thermometers infrequently measure tympanic temperature (e.g. Shinozaki et al, 1988;Daanen, 2006;Easton et al, 2007;Lee et al, 2011).…”
Section: Tympanic-membrane Temperaturementioning
confidence: 99%
“…Additionally, it has been reported that rectal temperature is affected by physical activity of the legs and arms ( 1 ). This signifi cant point is further emphasized by a very recent work that has demonstrated quite different rectal temperature measurements depending upon the depth of insertion of the rectal probe ( 15 ). Of further note, as mentioned above, it is usual for motor sports athletes to wear a cooling suit unit around the chest and to allow drinking during the race.…”
Section: Driver #01mentioning
confidence: 92%
“…Workers and fi eld athletes in hot environments can also suffer from serious heat strain problems, and some recent studies have been aimed at monitoring T c continuously in such situations ( 5 , 15 , 22 ). In particular, it has been reported that tympanic temperature is valid as a thermal index to evaluate the heat strain of workers who are wearing encapsulated personal protective clothing with a hood in hot environments ( 15 ), or a protective helmet in aircrew ( 21 ), and workers engaged in physical labor in hot environments ( 22 ). Thus, when considering the most suitable place to measure temperature to detect heat strain in racing car drivers quickly, reliably, and conveniently without undue encumbrance, tympanic temperature is one of the most likely potential candidates.…”
mentioning
confidence: 99%
“…Various physiological parameters for assessing the heat strain include core body temperature (T cr ), Heart Rate (HR), dehydration and Urine Specific Gravity (USG) [21]. HR is a primary indicator for a physiological strain especially during work and rest [22]. The oral, eardrum, rectal and the urine temperatures can be recorded as T cr [23]; an important criterion for the adverse health effects.…”
Section: Introductionmentioning
confidence: 99%